Micro and Macro Pragmatic Analysis of Ayatollah Al-Sistani’s Guidelines to Fighters against ISIS - Mohammed Abbass Shenaishel; Azhar Hassan Sallomi (مجلة الباحث, 2025)
The present paper is an analysis of the language of Ayatollah al Sistani’s guidelines to fighters against ISIS from micro and macro pragmatic perspective. It aims to detect the micro pragmatic components namely implicature and politeness utilized in this discourse and show how they convey in their layers the speaker’s intentions. In addition, it aims to reveal the spiritual and moral values offered in these guidelines. The researchers follow a qualitative method of analysis based on Grice’s model (1989) of implicature, Brown and Levinson’s (1987) theory of politeness, and Cap’s model of macro pragmatics. The paper concludes that speaker dedicates the conventional and conversational implicatures to express the idea of fighters’ rights and the necessity of the government’s support. Besides employing positive politness strategies like establishing common ground and using nicknames, he devotes the negative politeness strategies such as hedging and apologies for maintaining harmony within the listeners. Further, analyzing the discourse from macro-pragmatic perspective reveals various honorable themes like religious and patriotic duty, sacrifice and ethical conduct in warfare.